TARAS SHEVCHENKO AND UKRAINIAN ARCHAEOLOGY - Гоян, І. М.; Коваль, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This publication raises an important problem of T. Shevchenko’s role in the development of Ukrainian archaeological science. On the broad archival and artistic material the authors of the article prove that Kobzar’s poetic and painting heritage often had impulsts from hopes of national history, our archaeological past.